Influence of testing parameters on the determination of the bond strength of mortar renderings - Costa, Eliane Betânia Carvalho (ANTAC - Associação Nacional de Tecnologia do Ambiente Construído, 2009)
The testing of tensile bond strength, one of the main parameters to evaluate the performance of mortar renderings, is prescribed by different national and international standards. However, the existence of conflicting or under-specified parameters causes high variability of results for the same test situation. Hence, the aim of this study is to evaluate the influence of certain test parameters in the variability of the results for bond strength. The study was done in two stages: using a computer model using the Finite Element Method (Ansys® program), and an experimental study (in a laboratory), by doing tensile bond strength tests on mortar renderings applied on concrete slabs, with a total of 530 specimens. The results show that the geometry and dimension of the test specimen, the cutting procedure, the equipment type, loading rates and eccentricity contribute to the variability of the results. Additionally, there was a direct relationship between bond strength and the moisture of the rendering at the time the test was undertaken.